The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/etc.4018
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam honey bee colony feeding study: Linking effects at the level of the individual to those at the colony level

Abstract: Neonicotinoid insecticides have been used globally on a wide range of crops through seed treatment as well as soil and foliar applications and have been increasingly studied in relation to the potential risk to bees because of their detection in pollen and nectar of bee-attractive crops. The present article reports the results of laboratory studies (10-d adult and 22-d larval toxicity studies assessing the chronic toxicity of thiamethoxam to adult honey bees and larvae, respectively) and a colony feeding study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
5
25
1
Order By: Relevance
“…Colony overwinter survival and cluster size was significantly decreased by exposure to 100 ng/g of THI (Figures 2a and 3a). Our results agree with the colony-level feeding studies of Thompson et al (2019) [5] and Overmeyer et al (2018) [20], who found that colonies fed 100 ng/g of THI during six weeks in summer had significant (50%) reductions in number of adult bees relative to controls prior to overwintering and a significant, two times increase in overwinter mortality, but colonies fed lower doses of THI (12.5-50 ng/g THI) had no long-lasting colony effects.…”
Section: Effects Of Thiamethoxam On Overwintering Colonies Of Apis Mesupporting
confidence: 94%
See 4 more Smart Citations
“…Colony overwinter survival and cluster size was significantly decreased by exposure to 100 ng/g of THI (Figures 2a and 3a). Our results agree with the colony-level feeding studies of Thompson et al (2019) [5] and Overmeyer et al (2018) [20], who found that colonies fed 100 ng/g of THI during six weeks in summer had significant (50%) reductions in number of adult bees relative to controls prior to overwintering and a significant, two times increase in overwinter mortality, but colonies fed lower doses of THI (12.5-50 ng/g THI) had no long-lasting colony effects.…”
Section: Effects Of Thiamethoxam On Overwintering Colonies Of Apis Mesupporting
confidence: 94%
“…Similar to our study, Overmeyer et al (2018) [20] observed that high dose, 100 ng/g THI-exposed colonies consumed less syrup compared to lower-dose THI treatments and controls. Decreased colony strength and population size may explain the decrease in syrup consumption and overwinter weight loss (reflecting consumption of overwinter food stores) of the 100 ng/g THI-treated colonies in our study (Figures 4a and 5a).…”
Section: Effects Of Thiamethoxam On Overwintering Colonies Of Apis Mesupporting
confidence: 92%
See 3 more Smart Citations